The Collection All Around : Sharing Our Cities, Towns, and Natural Places. - Davis, Jeffrey T. (American Library Association, 2017)
Public libraries' mission, skills, and position in their communities make them ideal facilitators of public access to local resources. In other words, the collection is all around, and libraries can help citizens discover historical, cultural, and natural riches that they might otherwise overlook.